Identifikasi Jenis Lamun (Seagrass) Menggunakan Metode Transek Kuadran di Pantai Wisata Sarawandori - Roy Marthen Rahanra; Susanti Fakaubun; Yenniwati Sinaga; Yusuf Karllos Numberi (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
Seagrass plays an important role in coastal communities because it is one of the factors that supports the diversity of flora and fauna, influences the productivity of coastal waters, helps stabilize sediments, controls water clarity and quality and can also affect other surrounding ecosystems. The purpose of this study was to determine the types of seagrass in the coastal waters of Sarawandori village tourism, Kosiwo District, Yapen Islands Regency, Papua Province. This study used the quadrant transect method and compared the types found using an identification book. The results showed that the types of seagrass found were Cymodocea rotundata, Cymodocea serrulate, and Thallasia hemprichii and the most common species found was Cymodocea serrulate.